Prevalence And Description Of Lower Extremity Peripheral Artery Disease Based On Abi Value In Elderly Inpatient At Ukrida Hospital - Patty, Kevin Emmanuel; Kurniadhi, Didi; Winaktu, Gracia JMT (Universitas Kristen Krida Wacana, 2024)
Peripheral artery disease (PAD) is a disease caused by blockage of blood vessels by fat that occurs in the lower extremities with symptoms of pain in the lower extremities and intermittent claudication. PAP occurs in patients aged 60 years and over with risk factors of diabetes, smoking and hypertension. PAP can be detected through an Ankle Brachial Index (ABI) examination. This study aims to determine the description and prevalence of PAD based on ABI values ​​in elderly people hospitalized at UKRIDA Hospital, West Jakarta. The research is observational using a descriptive research design with a cross-sectional approach. Sampling is in the form of consecutive sampling, where all elderly people hospitalized at UKRIDA Hospital will be taken as research samples according to the inclusion criteria until they meet the minimum threshold. Using the Lemeshow formula, the sample size was 76 elderly people. The results of the study showed that the prevalence of PAD was 10.5% with the gender that suffered the most from PAP being women, 6 elderly people (75%) and 2 elderly men (25%). Risk factors for PAD sufferers include hypertension (62.5%), diabetes mellitus (37.5%), smoking (25%), and obesity (12.5%). The ABI results in PAD elderly were 2 mild ABI (0.75-0.9) (25%) and 6 severe ABI (<0.9%) (75%). Using the Fontaine classification, the clinical manifestations of PAD elderly were 7 at level I (87.5%) and 1 at level IV (12.5%).